Fabric and Garment Drape Measurement - Part 2 (Journal of Fiber Bioengineering and Informatics, 2013)
Fabric and garment drape were compared using an alternative drape measurement system based on animage analysis technique. Garment drape was investigated using dresses suspended on a mannequin.A graphical user interface was developed to carry out the image analysis and to calculate drape valuesidentifying and determining 21 parameters. A range of fabrics including knitted, woven and nonwovenfabrics were compared in terms of FAST properties, drape coefficient and drape values. Visual assessmentof the fabric range was carried out in terms of drape amount and preference. Low agreement was foundbetween individuals with regard to preferred drape amount and high agreement with respect to actualdrape amount. Nonwovens were found of better preference over some traditional fabrics. Most of thedrape values of fabric and garment were found to have poor correlations.
Keywords: Drape; Fabric; Garment; Drape Values; Image Analysis